2018
DOI: 10.1016/j.jneb.2017.09.013
|View full text |Cite|
|
Sign up to set email alerts
|

A Supermarket Double-Dollar Incentive Program Increases Purchases of Fresh Fruits and Vegetables Among Low-Income Families With Children: The Healthy Double Study

Abstract: Objective: To carry out a pilot study to determine if a supermarket double-dollar fruit and vegetable (F&V) incentive increases F&V purchases among low-income families Design: Randomized controlled design. Purchases were tracked using a loyalty card that provided participants with a 5% discount on all purchases during a 3-month baseline period followed by the 4-month intervention. Setting: A supermarket in a low-income rural Maine community Participants: 401 low-income and SNAP supermarket customers Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 25 publications
1
75
0
Order By: Relevance
“…Nineteen studies examined the impact of supermarket fruit and vegetable subsidies, incentives, vouchers, or prescriptions targeted towards low-income households or individuals [ 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Results from randomized trials and natural experiments consistently demonstrate increases in household fruit and vegetable purchases or adult fruit and vegetable intake when incentives are targeted towards SNAP participants [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]; yet, few studies have been conducted with children [ 52 ]. Studies assessing substitution found little evidence that fruit and vegetable incentives changed unhealthful food intake or expenditures [ 51 , 52 , 53 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies examined the impact of supermarket fruit and vegetable subsidies, incentives, vouchers, or prescriptions targeted towards low-income households or individuals [ 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Results from randomized trials and natural experiments consistently demonstrate increases in household fruit and vegetable purchases or adult fruit and vegetable intake when incentives are targeted towards SNAP participants [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]; yet, few studies have been conducted with children [ 52 ]. Studies assessing substitution found little evidence that fruit and vegetable incentives changed unhealthful food intake or expenditures [ 51 , 52 , 53 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has shown that offering subsidies and discounts for produce increases fruit and vegetable purchases among SNAP participants shopping in supermarkets and farmer markets. (19)(20)(21)(22)(23)(24)(25) The most prominent example is USDA's Healthy Incentives Pilot (HIP), which offered SNAP participants an incentive of 30 cents for every dollar of SNAP bene ts that they spent on eligible fruits and vegetables in participating supermarkets. (21) Spending on eligible fruit and vegetables increased by 11% and consumption of fruit and vegetables increased by 26% in HIP households compared to non-HIP households.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20) Researchers have also tested the impact of nancial incentives in supermarket settings, and have found that matching credits and discounts lead to higher spending on fresh fruits and vegetables among eligible customers. (21)(22)(23)(24)(25) Mobile produce markets may be an acceptable setting for SNAP incentive programs because they concurrently address physical access barriers to healthy food retailers and incorporate elements of community engagement in their program design. Though mobile produce markets are a promising strategy for mitigating nancial barriers to healthy food consumption, few, if any, studies have examined whether SNAP participants purchase more fruit and vegetables as a result of receiving nancial incentives in a mobile produce market setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence, including from randomized interventions, demonstrates that lowering the price of healthier food through subsidies increases their purchase and consumption across various settings and populations 11‐15 . Such analyses suggest that federal expansion of a 30% F&V subsidy to the broader US population could prevent more than 30,000 cardiovascular deaths annually 16 .…”
mentioning
confidence: 99%